Implementasi Participatory Action Research dalam Pemberdayaan UMKM Desa Plemahan melalui Digital Marketing - Sufaidah, Siti; Aris Widya, Moh. Anshori; Anandita, Septian Ragil; Masyhari, M. Fikri; Ubaidillah, Ubaidillah; Danan Joyo, Sabekti Siwi; Syafi’udin, Ahmad (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
The rapid development of information technology offers significant opportunities for micro-enterprises to increase competitiveness through digital marketing, yet limited digital literacy remains a major challenge in rural communities. This community service program was carried out in Plemahan Village, Sumobito District, Jombang Regency, focusing on empowering women of the PKK community and micro-enterprise owners. The program aimed to enhance community skills in utilizing social media and online marketplaces for product marketing, to foster digital literacy awareness, and to encourage the establishment of a technology-based learning community. The method applied was Participatory Action Research, involving participants in every stage from planning, training, mentoring, to evaluation. The results indicated a significant improvement in participants’ understanding of digital marketing concepts, technical skills in creating business accounts, and the quality of promotional content. In addition, the program led to social changes such as the formation of a digital marketing learning group and the emergence of local leaders supporting program sustainability. This initiative demonstrates that a participatory technology-based approach can serve as an effective strategy to strengthen rural community economies in the digital era.